2014
DOI: 10.1515/jpem-2013-0056
|View full text |Cite
|
Sign up to set email alerts
|

A novel genetic mutation in a Portuguese family with GCK-MODY

Abstract: Finding the same mutation in three different generations of diabetic patients, in the same family, is highly suggestive of its pathogenicity. To the authors' knowledge, this is the first time it is described in the literature. Correct molecular diagnosis of MODY predicts better the clinical course of diabetes and facilitates individualised management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We originally posed the question of what is the impact of pharmacological and non-pharmacological glucose lowering therapy in GCK-related hyperglycemia. However, we identified only one case report that presented data on active pharmacological intervention 12 and one study on dietary intervention 13 and the rest of the 10 studies [14][15][16][17][18][19][20][21][22][23] assessed the impact of stopping anti-hyperglycemic agents on HbA1c or glucose or assessed the stability of HbA1c over time on no therapy (Table 3). Thus, we concentrated on analyzing the evidence to support or refute non-treatment of GCK-related hyperglycemia.…”
Section: A) Gck-related Hyperglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…We originally posed the question of what is the impact of pharmacological and non-pharmacological glucose lowering therapy in GCK-related hyperglycemia. However, we identified only one case report that presented data on active pharmacological intervention 12 and one study on dietary intervention 13 and the rest of the 10 studies [14][15][16][17][18][19][20][21][22][23] assessed the impact of stopping anti-hyperglycemic agents on HbA1c or glucose or assessed the stability of HbA1c over time on no therapy (Table 3). Thus, we concentrated on analyzing the evidence to support or refute non-treatment of GCK-related hyperglycemia.…”
Section: A) Gck-related Hyperglycemiamentioning
confidence: 99%
“…Most studies on GCK-related hyperglycemia looked at within individual stability of HbA1c over time without glucose lowering therapy (175 individuals from case reports and cohort data, range of time between 3-126 months) 14,16,18,[20][21]23 or after cessation of pharmacologic therapy following genetic diagnosis (35 individuals from case reports and cohort data) 15,[19][20][22][23] . All studies showed stability of HbA1c with no significant change including when glucose lowering therapy of either oral hypoglycemic agents (OHA) or insulin was discontinued (table 3).…”
Section: A) Gck-related Hyperglycemiamentioning
confidence: 99%